2002
DOI: 10.1255/jnirs.347
|View full text |Cite
|
Sign up to set email alerts
|

Use of near Infrared Reflectance Spectroscopy to Analyse Bovine Faecal Samples

Abstract: Near infrared (NIR) reflectance spectroscopy was used to predict nitrogen (N), acid detergent fibre (ADF), neutral detergent fibre (NDF) and chromium (Cr) in beef faecal samples. One hundred and twenty faecal samples were scanned in a NIRSystems 6500 monochromator instrument over the wavelength range of 400–2500 nm in reflectance. Calibration equations were developed using modified partial least squares (MPLS) with internal cross validation to avoid overfitting. The coefficient of determination in calibration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 12 publications
3
10
0
Order By: Relevance
“…Our validation statistics were close to or within the range of those reported previously using dried ground cattle faeces for starch [R 2 val = 0.89 (SEP = 1.09) compared with 0.91 (SEP = 0.57) (Fredin et al 2014)], N [R 2 val = 0.80 (SEP = 0.10) compared with 0.78 (SEP = 0.08) to 0.83 (SEP = 0.10) (Purnomoadi et al 1996;Cozzolino et al 2002)], NDF [R 2 val = 0.84 (SEP = 0.98) compared with 0.85 (SEP = 0.80) (Cozzolino et al 2002)], and ADF [R 2 val = 0.92 (SEP = 0.95) compared with 0.74 (SEP = 0.80) to 0.96 (SEP = 0.12) (Purnomoadi et al 1996;Cozzolino et al 2002)] but poorer for ADL [R 2 val = 0.87 (SEP = 0.96) compared to 0.94 (SEP = 0.15) (Purnomoadi et al 1996)]. The comparatively low R 2 val for N (0.80) is likely due to the small variation (2.24%-3.17%) in reference values for this faecal constituent.…”
Section: Populationsupporting
confidence: 89%
“…Our validation statistics were close to or within the range of those reported previously using dried ground cattle faeces for starch [R 2 val = 0.89 (SEP = 1.09) compared with 0.91 (SEP = 0.57) (Fredin et al 2014)], N [R 2 val = 0.80 (SEP = 0.10) compared with 0.78 (SEP = 0.08) to 0.83 (SEP = 0.10) (Purnomoadi et al 1996;Cozzolino et al 2002)], NDF [R 2 val = 0.84 (SEP = 0.98) compared with 0.85 (SEP = 0.80) (Cozzolino et al 2002)], and ADF [R 2 val = 0.92 (SEP = 0.95) compared with 0.74 (SEP = 0.80) to 0.96 (SEP = 0.12) (Purnomoadi et al 1996;Cozzolino et al 2002)] but poorer for ADL [R 2 val = 0.87 (SEP = 0.96) compared to 0.94 (SEP = 0.15) (Purnomoadi et al 1996)]. The comparatively low R 2 val for N (0.80) is likely due to the small variation (2.24%-3.17%) in reference values for this faecal constituent.…”
Section: Populationsupporting
confidence: 89%
“…For these materials, the NDSol mean values (100-48.6 = 51.4 g 100 g -1 ) were about twice our values, whereas the SD associated with NDF were much lower than ours. These fi gures explain why the SEC associated with our NDSol was almost twice that reported for bovine manure (1.35 g 100 g -1 ) 33 or mushroom compost (1.33 g 100 g -1 ). 47 In our study, SECV for NDSol was similar to that of temperate plant materials (3.82 g 100 g -1 ) 23 or dairy manure (2.8 g 100 g -1 ), 31 but higher than that of mushroom compost (1.14 g 100 g -1 ) 47 and (0.57 g 100 g -1 b.w.).…”
Section: Total Organic Matter Characteristics: Ash C Dumas N Dumas supporting
confidence: 55%
“…The SEC value of NKj obtained in this study was about twice that reported for Mediterranean leaves and litters (0.08 g 100 g -1 ) 20 and compost (0.07 and 0.03 g 100 g -1 ), 28,47 but was lower than that reported for other heterogeneous materials such as bovine manure (0.74 g 100 g -1 ). 33 The SECV of NKj can be compared with other studies: dairy manures (4.42, 0.23 and 0.05 g 100 g -1 ), [30][31]49 or compost (0.08 g 100 g -1 DM and 0.03 g 100 g -1 bulk weight). 28,47 RPD helps in comparing the calibrations from different studies (different population abundance and material homogeneity).…”
Section: Total Organic Matter Characteristics: Ash C Dumas N Dumas mentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18][19] The easiest thing to find, and therefore to survey is faeces, which are rich in chemical information that can be captured by NIR spectroscopy and reflect the dynamic and inherent physiology of the animal. [20][21][22] As an example, DNA analysis has been employed for population surveys of the Amur leopard (Panthera pardus orientalis) and Siberian tiger (Panthera tigris altaica) with some success. However, information from genetic material can be limited by the quality and quantity of DNA in the sample, as well as false alleles and allelic dropout in fragmented DNA obtained from in situ sources of biomaterials.…”
Section: Nir Spectroscopy Is Inherently Suited To Address Variation Imentioning
confidence: 99%